Identification of Place Theory in the Mutun Beach Tourism Area, Lampung - Pradivta, I Made Surya Putra; Persada, Citra (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
Abstract. Mutun Beach, located in the Padang Cermin District, Pesawaran Regency, Lampung Province, Indonesia, is one of the natural tourist attractions with great potential to increase the local revenue in Pesawaran due to its combination of white sand, clear sea water, and various exciting activities offered. However, a significant tourist decrease has occurred, especially during the COVID-19 pandemic. In addition, the presence of competing beach resort developers, poor road access, inadequate aesthetic design, and poor waste management are also reasons why Pantai Mutun is becoming less popular. The collaboration of the